Reconceiving Religious Conflict New Views from the Formative Centuries of Christianity - Mayer, Wendy; Wet, Chris L. de (Taylor & Francis, 2018)
Religious conflict in the ancient world|Religious persecution in the ancient world|Religious conflict in late antiquity|Religious persecution in late antiquity|Religious violence in late antiquity|Religious violence in the ancient world|Iconoclasm in the ancient world|Iconoclasm in the late antiquity|The Funerary Speech for John Chrysostom|John of Ephesus's Church History|Disability and early christianity|Deformity and early christianity|Religious persecution and early christianity|Religious violence and early christianity|Religious conflict and early christianity|pseudo-Clementine Homilies|Religious Violence in Late Antique Egypt|destruction of the Serapeum at Alexandria|Abbot Shenoute|Closure of temple of Isis Philae|Panopolis|Cologne Mani Codex|Manichaean Kephalaia|Gnostic-Manichaean Christianity|Hagiasma of Chonai|Jan Bremmer|Pieter J. J. Botha|Chris L. de Wet|Christine Shepardson|Alan H. Cadwallader|Christoph Stenschke|Maijastina Kahlos|Jitse H. F. Dijkstra|Peter Van Nuffelen|Elizabeth DePalma Digeser|Gerhard van den Heever